A failure to show the efficacy of a dot‐probe attentional training in dysphoria: Evidence from an eye‐tracking study. Issue 12 (13th June 2018) - Duque, Almudena; Vazquez, Carmelo
Abstract: Objective: This study examines whether a 4‐day dot‐probe attentional training to orient attention toward positive words could lead participants with dysphoria to change selective attention to emotional faces. It was also explored whether this positive attentional bias training could lead to a decrease in depressive symptoms. Methods: Participants were randomly assigned to Positive Training Group (PTG) and No Training Group (NTG). PTG was composed of 16 subjects, whereas NTG was composed of 15 subjects. All participants were women with a mean age of 22.87 ( SD  = 3.21). Results: Results showed that dysphoric participants in the PTG did not show changes in attentional patterns to emotional faces. Furthermore, depressive symptoms did not significantly change after the 4‐session training. Conclusions: These results suggest that cognitive training procedures based on dot‐probe paradigms are probably not adequate to modify attentional patterns in individuals with depressive symptoms. The theoretical and practical implications are discussed.